Development of a Meniscal Ossicle After a Meniscal Root Repair Augmented with Bone Marrow Aspirate Concentrate: A Case Report. Issue 1 (January 2020) - Eliasberg, Claire D.; Lin, Kenneth M.; Bauer, Thomas W.; Rodeo, Scott A.
Abstract : Case: A 17-year-old boy had persistent knee pain 1 year after medial meniscal root repair augmented with bone marrow aspirate concentrate injection. Radiographs and magnetic resonance imaging (MRI) demonstrated an intrameniscal ossicle which was not present on MRI performed before 6 months. He underwent arthroscopic excision of the meniscal ossicle. At the 7-month follow-up, he had complete relief of his pain. Conclusions: It is possible that the meniscal ossicle developed because of osteoinductive cells and cytokines from the injected bone marrow or the drill hole for root repair and should be considered as a possible complication of this procedure.